Analisis Kemampuan Guru dalam Mengimplementasikan Pembelajaran Tematik Kelas Rendah SD Inpres 6/86 Biru - Ayu Lestari; Awaluddin Muin; Sitti Jauhar (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
Abstract; This research is a descriptive qualitative research which aims to determine the teacher's ability to implement thematic learning for the lower grades of SD Inpres 6/86 Biru. The subjects of this study were lower grade teachers, namely grade I, II, and III teachers. Research data obtained from interviews, observations, and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results of this study indicate that the abilities of low-grade teachers still cannot be categorized as having good abilities. This can be known based on the stages carried out, namely the stages of planning, implementing and conducting an assessment. The three stages are carried out by the teacher but are not maximized, this can be seen at the planning stage the teacher has used the theme but there are still components that are not visible in the lesson plans. The implementation phase consists of opening activities, core activities and closing activities. The teacher has carried out these activities, but not optimally. The last stage is the assessment stage, at this stage the teacher still has not implemented it optimally.